Prognostic impact of elective tracheotomy in resected oral cavity squamous cell carcinoma: A nationwide cohort study - Ku‐Hao Fang; Chung‐Jan Kang; Li‐Yu Lee; Shu‐Hang Ng; Chien‐Yu Lin; Wen‐Cheng Chen; Jin‐Ching Lin; Yao‐Te Tsai; Shu‐Ru Lee; Chih‐Yen Chien; Chun‐Hung Hua; Cheng Ping Wang; et al. (Cancer Medicine, 2024)
Abstract Background Elective tracheotomy is commonly performed in resected oral squamous cell carcinoma (OCSCC) to maintain airway patency. However, the indications for this procedure vary among surgeons. This nationwide study evaluated the impact of tracheotomy on both the duration of in‐hospital stay and long‐term survival outcomes in patients with OCSCC. Methods A total of 18,416 patients with OCSCC were included in the analysis, comprising 7981 patients who underwent elective tracheotomy and 10,435 who did not. The primary outcomes assessed were 5‐year disease‐specific survival (DSS) and overall survival (OS). To minimize potential confounding factors, a propensity score (PS)‐matched analysis was performed on 4301 patients from each group. The duration of hospital stay was not included as a variable in the PS‐matched analysis. Results Prior to PS matching, patients with tracheotomy had significantly lower 5‐year DSS and OS rates compared to those without (71% vs. 82%, p < 0.0001; 62% vs. 75%, p < 0.0001, respectively). Multivariable analysis identified tracheotomy as an independent adverse prognostic factor for 5‐year DSS (hazard ratio = 1.10 [1.03–1.18], p = 0.0063) and OS (hazard ratio = 1.10 [1.04–1.17], p = 0.0015). In the PS‐matched cohort, the 5‐year DSS was 75% for patients with tracheotomy and 76% for those without (p = 0.1488). Five‐year OS rates were 66% and 67%, respectively (p = 0.0808). Prior to PS matching, patients with tracheotomy had a significantly longer mean hospital stay compared to those without (23.37 ± 10.56 days vs. 14.19 ± 8.34 days; p < 0.0001). Following PS matching, the difference in hospital stay duration between the two groups remained significant (22.34 ± 10.25 days vs. 17.59 ± 9.54 days; p < 0.0001). Conclusions While elective tracheotomy in resected OCSCC patients may not significantly affect survival, it could be associated with prolonged hospital stays.